Nutritional risk assessment of Critically Ill patients based on NUTRIC score at Shifa International Hospital, Islamabad - Bibi, Zainab; Safdar, Mahpara; Khan, Rezzan (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the nutritional risk of critically ill patients. Method: The single-centre, prospective, observational study was conducted at the Shifa International Hospital, Islamabad, Pakistan, from November 9, 2020, to May 8, 2021, and comprised critically ill patients of either gender admitted to pulmonology, neurology, nephrology, cardiology, gastroenterology and general intensive care units. They were subjected to screening using the Nutritional Risk of Critically Ill tool, and the risk was categorised as moderate and high. Data was analysed using SPSS 23. Results: Of the 88 patients, 58 (66%) were males. The overall mean age of the sample was 62.71±12.62 years. The nutritional risk was moderate in 39(44%) patients and high in 49(56%). The mean Acute Physiology, Age and Chronic Health Evaluation II score, Sequential Organ Failure Assessment score and Nutritional Risk of Critically Ill was 16.73±4.34, 5.91±1.92 and 5.71±1.41, respectively. There was a significant association of nutritional risk with age (p=0.04) and Sequential Organ Failure Assessment score (p<0.001). Biochemical markers were different between those with high risk and patients with moderate risk (p<0.05). Conclusion: The overall prevalence of malnutrition in critically ill patients was high which may further affect clinical outcomes. Key Words: Nutritional status, Malnutrition, Nutritional assessment, Risk assessment.